STUDI PENGEMBANGAN OBJEK WISATA GOA BATU KAPAL KECAMATAN SANGIR BALAI JANGGO KABUPATEN SOLOK SELATAN - Yurnia Alex Sander; Sri Mariya (JURUSAN GEOGRAFI FIS UNP, 2023)
This study aims to determine the internal factors of Goa Batu Kapal tourism object, explain external factors in Goa Batu Kapal tourism object, explain the development of Goa Batu Kapal tourism object which will be carried out in the future. The method used in this study is a qualitative research method. Key informants were taken from the tourism office, the sub-district head and the guardian of Nagari Sungai Kunyit Barat. From the key informants, informants were taken consisting of the public and visitors to the Batu Kapal Cave tourist attraction. Data analysis was carried out by reducing, presenting and drawing conclusions.The results of the study indicate the identification of internal factors as supporting and inhibiting the development of the Batu Kapal tourist attraction. Goa Batu Kapal has the beauty of a cave that is still beautiful, has a very beautiful and colorful cave shape that spoils the eyes of tourists and for tourists who like to take pictures can also get a good view in the cave so that tourists feel satisfied and can come back to visit this tour . The weakness of the Batu Kapal Cave tourist attraction is the lack of quality facilities and infrastructure such as trash cans, signposts, and poor road conditions, etc. identification of external factors are factors that support and inhibit the development of the Batu Kapal tourist attraction, namely Batu Kapal Cave which is located close to the center of South Solok Regency, making it easier for tourists from outside the area to visit the tourism object. The inhibiting factor is threats (threaths), where Batu Caves access to the cave tourist area is still very bad, the conditions are still muddy and hollow and also the connecting bridge between one cave and other caves has begun to be fragile, besides that weather conditions are very influential on tourists who will stand tall. if it rains, it is certain that there will be no tourists visiting Batu Kapal Cave. Development of Goa Batu Kapal Tourism Object, the first is access, development in terms of access in order to repair potholes and provide easy-to-understand directions, secondly the accommodation needed for Batu Kapal Cave attractions such as hotels, homestays, or inns, There is a need for a post - health posts in the Batu Kapal tourist attraction area, Batu Kapal cave tourist attraction is guarded by local youths who are on guard for tourists to get security services, Development of worship facilities which are currently not equipped with sufficient prayer mats and dirty toilets, needs improvement to make it easier for tourists to worship.